Detection of [C i] Emission in Nebular Spectra of a Peculiar Type Ia Supernova 2022pul - Liu, Jialian; Wang, Xiaofeng; Yang, Yi; Filippenko, Alexei V.; Brink, Thomas G.; Zheng, WeiKang; Zhang, Jujia; Li, Gaici; Yan, Shengyu (Astrophysical journal. Letters, 2025)
SN 2022pul gains special attention due to its possible origin as a super-Chandrasekhar-mass white dwarf (WD) explosion (also called a 03fg-like Type Ia supernova), which shows prominent [O i ], [Ne i ], and [Ca ii ] lines in its late-time spectra taken at ∼+300 days after the time of peak brightness. In this Letter, we present new optical observations of this peculiar object, extending up to over 500 days after peak brightness. In particular, in the t ∼ +515 days spectrum, we identified for the first time the presence of narrow emission from [C i ] λλ 9824, 9850, which appears asymmetric and quite similar to the accompanied [O i ] λ 6300 line in strength and profile. Based on the violent merger model that accounts well for previous observations but leaves little carbon in the center of the ejecta, this carbon line can be reproduced by increasing the degree of clumping in the ejecta and setting the carbon mass the same as that of oxygen (∼0.06 M ⊙ ) in the innermost region (≲2000 km s −1 ). In principle, the central carbon could come from the secondary WD if it is ignited when hit by the shock wave of the explosion of the primary WD and explodes as a Ca-rich supernova, whereas pure deflagration of a super-Chandrasekhar-mass WD can account for such unburnt carbon more naturally.